Building the architecture for sustainable space security : conference report 30-31 March 2006. (UNIDIR, 2006)
This 2006 conference is the latest in a series of annual conferences held since 2002 by the United Nations Institute for Disarmament Research in cooperation with a wide range of member states, research institutes and NGOs. Participants at the conference discussed the current threats posed to the peaceful uses of outer space, both from the impact of technological developments and of political/military decisions. This publication contains a report on the proceedings of the conference.--Publisher's description.